Inter-capsule fusion and capsule shell destruction using dynamic covalent polymers. Issue 18 (28th April 2021) - Wang, Yifei; Quevedo, Khamila; Pentzer, Emily
Abstract : Herein, capsule shells containing hindered urea bonds were prepared using interfacial polymerization in an oil-in-oil Pickering emulsion stabilized by functionalized graphene oxide nanosheets. Abstract : Herein, capsule shells containing hindered urea bonds were prepared using interfacial polymerization in an oil-in-oil Pickering emulsion stabilized by functionalized graphene oxide nanosheets. After isolation and mild heating, the polymer shells can be fused into monoliths or destroyed. These dynamic polymer shells provide a route to control the morphology of composite materials with application in energy storage, separations, additive manufacturing, controlled release, and so on.